AB0056 Emerging role of IL-33/ST2 axis in endothelial cell injury of lupus nephritis. (15th June 2017) - Yu, S; Tao, Y
Abstract : Background: "Alarmins" are prototypic endogenous pro-inflammatory factors as they are released from necotic cells and provoke local damage or systemic inflammation. Evidences are accumulating to support the inclusion of "Alarmins" as targets of autoreactivity as well as inducers in the pathogenesis of Systemic Lupus Erythematosus (SLE). Interleukin (IL)-33 is a novel member of the family of "Alarmins" because of its characteristics and functions in mediating host immune responses. On this background, we sought to determine the role of IL-33/ST2 axis in lupus pathogenesis. The role of IL-33/ST2 axis has not previously been described in lupus nephritis. Objectives: This project will study the followings: (1) To determine whether IL-33 was present in renal glomerular endothelial cells; (2) To assess the functional and intracellular signal transuction mechanisms regulating the link between IL-33/ST2-mediated innate immunity and inflammation in CD4 + T cells-endothelial cells co-culture system of lupus patients. Results: Immunofluorescence (IF) for IL-33 in the kidney were performed in both MRL lpr lupus mice and C57BL/6J mice. On double staining for IL-33 and lectin, IL-33 was clearly seen in glomeruli and also in peritubular areas. To determine whether the IL-33 staining in glomeruli and peritubular areas was in endothelium, double IF staining for IL-33 and von Willebrand factor (vWF) was performed. IL-33 co-localized with vWF in glomeruli and in peritubular areas. The increased levels of IL-33 mRNA transcripts were detected in kidney of MRL lpr lupus mice compared with C57BL/6J mice. Expression of cell-surface ST2 was increased on the CD4 + T cells of lupus patients when compared with healthy controls. Serum sST2 level was significantly higher in SLE patients with flare than those without flare (p<0.05). Conclusions: As a result of external stimuli or infection, renal glomerular endothelial cells undergo cellular death and release the "Alarmin", IL-33, to alert the lupus immune system. Released IL-33 interact with their target cells, CD4 + T cells via their specific receptor ST2 to subsequently induce innate and adaptive responses, activate inflammatory pathways in the pathogenesis of lupus nephritis. Disclosure of Interest: None declared